BIOSINTESIS NANOPARTIKEL PERAK MENGGUNAKAN EKSTRAK BUAH Passiflora flavicarva (MARKISA) UNTUK MENDETEKSI LOGAM BERAT - Dina Maryani; M. Lutfi Firdaus; Nurhamidah Nurhamidah (University of Bengkulu, 2017)
The aim of this research was to synthesize silver nanoparticle (NPP) by using Passiflora flavicarva (Markisa) fruit extract as detector of heavy metal. The NPP particles produced were determined by their optimum condition on the ratio of the volume of Passiflora flavicarva passion fruit extract to AgNO3 and the reaction time. The silver nanoparticles produced under optimum conditions will be tested for selectivity against several metals that are often present in the environment, once the selective metal is known then it can be sensitized to the metal using a UV-Vis spectrophotometer to determine the minimal concentrations that can be detected by the silver nanoparticles Formed. The results showed that Passiflora flavicarva passion fruit extracts could be used for the biosynthesis of NPP particles because they contain vitamin C and flavonoids capable of reducing Ag+ to Ag0 in the form of NPP. The optimal conditions for forming NPP particles are in the 1: 2 ratio with a 2 hour reaction time. From the results of selectivity test of NPP to some heavy metals that often exist in environment, it is known that NPP selective to mercury metal. It was found that selective mercury was followed by a sensitivity test with a UV-Vis spectrophotometer, with sensitive NPP up to a concentration of 6.7 ppm. From the results of this study it can be concluded that NPP particles formed can be used to detect mercury metal up to a minimum concentration of 6.7 ppm.